1993
DOI: 10.1093/oxfordjournals.humrep.a138103
|View full text |Cite
|
Sign up to set email alerts
|

Improved hatching in mouse embryos brought about by combined partial zona dissection and co-culture

Abstract: In this study 874 mouse embryos were allocated to six groups including a control, co-culture, and four groups that underwent partial zona dissection (PZD): at the 2-cell (PZD-2) and morula stages (PZD-M) both with and without co-culture. Rates of complete blastocyst hatching on day 5 increased in the following order: control, co-culture alone, PZD-2 alone, PZD-M alone, PZD-2 with co-culture and PZD-M with co-culture (P < 0.00001). PZD-M led to significantly higher rates of complete blastocyst hatching compared… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

1994
1994
2018
2018

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 0 publications
1
4
0
Order By: Relevance
“…However, historical comparison of two studies performed by the same group, where co-culture alone (Wiemer et al,, 1993) and AH + CC were performed, strongly suggests an additive beneficial effect of the two techniques combined. This agrees with the all-way comparison of standard culture, co-culture alone, AH-alone, and AH+CC in the mouse (Khalifa et al, 1993), where the combination AH + CC group outperformed all the other groups in terms of complete blastocyst hatching.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…However, historical comparison of two studies performed by the same group, where co-culture alone (Wiemer et al,, 1993) and AH + CC were performed, strongly suggests an additive beneficial effect of the two techniques combined. This agrees with the all-way comparison of standard culture, co-culture alone, AH-alone, and AH+CC in the mouse (Khalifa et al, 1993), where the combination AH + CC group outperformed all the other groups in terms of complete blastocyst hatching.…”
Section: Discussionsupporting
confidence: 88%
“…Cohen et al (1990) made the initial observation that a combination of assisted hatching and co-culture was apparently incompatible. However, subsequent study in the mouse (Khalifa et al, 1993) enabled a comparison of rates of blastocyst hatching relative to the use of assisted hatching and/or co-culture to be made, and showed that blastocyst hatching was optimally and additively enhanced by combination of both techniques. Also, combination of 2 days of co-culture and day 3 assisted hatching in human IVF has recently been shown not only to be feasible but also suggestive of being significantly advantageous to certain poor prognosis patients .…”
Section: Introductionmentioning
confidence: 99%
“…Next, matured oocytes were inseminated with heparin-treated (20 IU/ml) frozen-thawed bull spermatozoa. After 20 to 22 h zygotes were placed in co-culture with the bovine oviduct epithelial cell monolayer in Menezo B2 medium 4 (Khalifa et al, 1993) for 6 to 8 days to develop up to the blastocyst stage. Embryos at middle, late or expanded blastocyst stages were used.…”
Section: In Vitromentioning
confidence: 99%
“…By scraping the needle along the holding pipette the external surface of the zona pellucida was broken along the area where the needle was inserted. This procedure of the partial zona disection was based, in part, on the method used by Malter and Cohen (1989) and Khalifa et al (1993).…”
Section: Perforating the Zona Pellucidamentioning
confidence: 99%
“…Zygotes produced after subzonal injection of human spermatozoa showed a greater potential for development to cleaved embryos and pregnancy when cocultured with Vero cells (12). Utilization of coculture after partial zona dissection of mouse embryos has resulted in greater numbers of hatched blastocysts (13). In a similar study embryos from couples with three or more failed attempts at IVF were treated with coculture on bovine oviduct epithelial cells (BOEC) followed by assisted hatching.…”
Section: Introductionmentioning
confidence: 99%